An altimetry based examination of the path and variability of the Agulhas Return Current - Fadida, Yotam (Department of Oceanography, 2019)
As a result of climate change, partially driven by anthropogenic activity, strengthening wind stress over the worlds oceans is yielding a western boundary intensification and pole-ward shift of oceanic currents (Yang, 2016). Shifting wind regimes and perturbations in neighboring currents have been associated with variations in the flow path of western boundary currents (WBC) and their extensions (Talley, 2011; Combes and Matano, 2014; Nakamura and Kazmin 2003). WBCs, typically characterised by fast flowing and warm currents, are key regions of heat and salt transport as well as for oceanic carbon uptake, air-sea heat flux and nutrient transport, thus positional shifts may have far-reaching implications (Gray and Palter, 2017). While meridional trends (latitudinal migrations) have been observed in analogous WBCs and their extensions, no long-term investigation (decadal) into the flow path and position of the Agulhas Return Current (ARC) has been carried out. Now, with over 25 years of altimetric, satellite remote observation data available, a better understanding of the flow path, seasonal cycle, meridional trends and eddy kinetic energy (EKE) of the ARC is possible. Here we provide a detailed description of the flow path of the ARC together with several mechanisms that may be contributing to the current’s apparent stability. In addition we demonstrate that the documented western boundary intensification and pole-ward shift may be manifesting itself in two ways in the ARC, an increase in regional EKE and a southward trend found mainly in the flow-path of the eastern section of the ARC. Our results show a strong link between the EKE of the region and the Subtropical Indian Ocean Dipole, both of which are associated with the Southern Annular Mode (SAM), illustrating the effects that southward shifts in the subtropical high pressure system have on regional and mesoscale climate modes. The combination of a stable, topographically forced flow path with observed EKE increases, demonstrate the effects of wind stress intensification on a region highly influenced by its bathymetry. Further research into the effects of enhanced eddy activity is necessary, as it has been shown to affect regional primary production (Falkowski, 1991; Oschlies, 1998) and air-sea interactions, thus having potential ramifications for regional aquaculture, weather and fisheries, as well as calculations/models concerned with heat-flux and carbon exchange.